Design and Performance Evaluation of an IoT-Based Teleoperated Shuttlecock Launcher for Dynamic Badminton Training - Muchamad Malik; Agus Mukhtar; Aan Burhanuddin; Rifki Hermana; Ibnu Toto Husodo; Dwi Yan Damar Arya Prananta; Subkhan Ma'mun (Fakultas Teknik Universitas Samudra, 2026)
Advanced badminton training requires dynamic attack simulations that are difficult to fulfill by human coaches or conventional static machines. This study aims to design, implement, and evaluate the performance of an interactive shuttlecock launcher prototype based on the Internet of Things using wireless remote control. The research method uses a quantitative experimental approach through research and development focused on mechanical actuation precision and network transmission reliability. Evaluations were conducted by measuring projectile launch speed and landing accuracy across six random court zones. The results showed a highly proportional mechanical precision with a maximum launch speed reaching three hundred and eight point five kilometers per hour. Spatial accuracy testing resulted in a mean absolute error of zero point twenty-two meters, which is technically advantageous as it simulates the uncertainty of human strokes due to aerodynamic drag. Network performance demonstrated an end-to-end latency of forty-five milliseconds and a data packet loss of zero point four percent, well below the human visual perception threshold of two hundred milliseconds. In conclusion, this system is proven to be highly responsive and capable of transforming a static launcher into a robotic extension for coaches, allowing instant manipulation of speed and direction to train athletes' anticipatory agility in real match conditions.